The Stakeholder Experience of a large scale final year undergraduate social community research project - Mann, Claire; Boyd, Matthew (2017)
Objective: In 2014 The School of Pharmacy at the University of Nottingham needed to deliver individual research methods supervision by a small number of academic staff to a large number of final year students. There are limited opportunities for students to gain patient facing experience on this course. The learning initiative was designed to meet these needs. Design: Dissertation students were offered a unique opportunity to participate in a large scale community pharmacy research project. Eighty-two students collected standardised data from patients across 36 pharmacies in the Greater Nottingham area. Local data collection supervision was provided by the local community pharmacists at the data collection sites. Academic supervision was provided to students using a hub and spoke model with ‘hub’ supervision provided by two members of staff offering broad methodological support to the cohort. This was further supported by local supervisors providing individualised ‘spoke’ support to students. Students were able to examine and report on their local results. The data generated overall provides a mass dataset for further examination by academics. An independent evaluation of stakeholder experience was undertaken. Assessment: Students were assessed by a poster presentation and written report summarising one segment of local analysis. Conclusion: Academics saw the hub and spoke model of supervision as innovative and a positive and efficient use of their time. All participating stakeholders feel that students benefit from the timely development of their transferable skills for their professional career; skills cited as requirements for pharmacy education by the GPhC (2011).